The effectiveness of chemo-radiotherapy programs of last generation in patients with hodgkin's lymphoma - E. A. Demina; O. P. Trofimova; G. S. Tumyan; E. N. Unukova; A. G. Borodkina; N. E. Kondratieva (Онкогематология, 2022)
We report the brief analysis of basic treatment directions for last 80 years and our own 30-years results of therapy (total: 566patients) under consistent treatment protocols. We determined the benefit ofpatients division on prognostic groups according to tumor burden for a treatment choice. It was demonstrated the advantage of modern chemo-radiotherapy programs of last generation over radical radiotherapy and chemotherapy, and also the combined modality programs of last generation over previous treatment options. Our data showed the ability to achieve the equally high results in all prognostic groups at carrying out of the modern combined modality programs of last generation without treatment regimen deviations: the 5-years overall survival was 98 %, 95 % and 90 % in favorable, intermediate and poor prognosis groups respectively. These outcomes were similar to results of the large research centers. Adequate planning of studies at introduction in practice new treatment programs is discussed.